2021
DOI: 10.1021/acs.est.1c01541
|View full text |Cite
|
Sign up to set email alerts
|

Nail Samples of Children Living near Coal Ash Storage Facilities Suggest Fly Ash Exposure and Elevated Concentrations of Metal(loid)s

Abstract: Children who live near coal-fired power plants are exposed to coal fly ash, which is stored in landfills and surface impoundments near residential communities. Fly ash has the potential to be released as fugitive dust. Using data collected from 263 children living within 10 miles of coal ash storage facilities in Jefferson and Bullitt Counties, Kentucky, USA, we quantified the elements found in nail samples. Furthermore, using principal component analysis (PCA), we investigated whether metal­(loid)­s that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 92 publications
0
3
1
Order By: Relevance
“…CCR air pollution is a known inhalation health hazard due to small airborne particulates (<0.25 μm diameter) and has been associated with higher morbidity and respiratory and cardiovascular disease. A growing body of survey-based studies has shown that children living near power plants may experience increased respiratory problems and neurobehavioral disorders. One recent study using direct measurements found an association between residence proximity to CCR disposal sites and the concentrations of Fe, Al, and silicon (Si) in children’s nails. The concentration of Cr, Mn, and zinc (Zn) in the children’s nails were also higher than literature-reported values for non-CCR exposed children …”
Section: Future Perspectivescontrasting
confidence: 60%
See 1 more Smart Citation
“…CCR air pollution is a known inhalation health hazard due to small airborne particulates (<0.25 μm diameter) and has been associated with higher morbidity and respiratory and cardiovascular disease. A growing body of survey-based studies has shown that children living near power plants may experience increased respiratory problems and neurobehavioral disorders. One recent study using direct measurements found an association between residence proximity to CCR disposal sites and the concentrations of Fe, Al, and silicon (Si) in children’s nails. The concentration of Cr, Mn, and zinc (Zn) in the children’s nails were also higher than literature-reported values for non-CCR exposed children …”
Section: Future Perspectivescontrasting
confidence: 60%
“…The concentration of Cr, Mn, and zinc (Zn) in the children's nails were also higher than literature-reported values for non-CCR exposed children. 164 More research using direct measurements are needed to quantify potential health impacts posed by CCRs. 160 This research should include direct measurements of soil, water, and contaminant body burdens.…”
Section: Fate and Risk Assessmentmentioning
confidence: 99%
“…A study by Zierold et al examined residents who lived within 10 miles (16 km—much larger than our study area) from a coal ash storage facility and used geospatial analysis to confirm that the participants with high iron (Fe), Al, and silicon (Si) (which loaded together in nails of children near coal ash storage facility, using PCA) lived closer to the coal ash storage facility. 74 A study of 39 children in Chicago observed higher toenail levels of Cd, Co, Fe, Mn, and V in children living near an industrial corridor than in children in a comparison community. 75 Future studies can build on this current study by examining metal concentrations in people near an oil drilling site and using a larger study radius or a control area.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are multiple other active and inactive oil drilling sites within 3 km of this study site, so we are unable to adequately assess variations in exposure, as participants living farther and/or upwind from this drill site might live a mile downwind from a different drill site. A study by Zierold et al examined residents who lived within 10 miles (16 kmmuch larger than our study area) from a coal ash storage facility and used geospatial analysis to confirm that the participants with high iron (Fe), Al, and silicon (Si) (which loaded together in nails of children near coal ash storage facility, using PCA) lived closer to the coal ash storage facility . A study of 39 children in Chicago observed higher toenail levels of Cd, Co, Fe, Mn, and V in children living near an industrial corridor than in children in a comparison community .…”
Section: Discussionmentioning
confidence: 99%
“…건강영 향 평가의 공간적 범위는 집단의 다양성 때문에 환경영향평가 의 대기 질, 악취 항목의 공간적 범위를 따르거나, 25) 개발사업 의 제한 범위를 참고로 하여 분석 범위를 정하는 경우가 많다. 국내 연구 사례의 경우 대기 및 산업 폐수로 환경오염물질이 노 출되는 광양만 산업단지 영향권을 5 km 이내로, 26) 대기 오염 을 통한 고농도 중금속에 노출되는 장항제련소는 4 km, 27) 대 기, 토양, 상수도 오염 등에 노출되는 포항 철강 산업단지는 15 km, 28) VOCs 대기 노출 지역인 청주 산단 영향권을 3 km 29) 로 분석하였으며 국외의 경우 비산재의 대기 오염 노출 영향을 받 는 석탄화력발전소 영향권을 발전소에서 2마일 간격으로 5개 구역으로 나누어 분석한 연구와 30) 매우 근거리(1 km 이하), 근 거리(1~3 km), 먼 거리(3~5 km)로 나누어 분석한 연구 31) 등 다 양한 사례가 있다.…”
unclassified